FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN POSYANDU LANSIA - idham latif; Rudiansyah Rudiansyah; Bagus Hera Ichwandie (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
Elderly is someone who has reached the age of 60 years and over. Posyandu for the elderly is a health service to serve the elderly. According to WHO data (2018), the world's elderly population aged 60 years and over will increase from 900 million to 2 billion in 2050. This study aims to determine the relationship between the level of knowledge, family support and the role of cadres in utilizing the posyandu for the elderly. This type of research uses a systematic literature review with the literature review method. The results of the study found that there was a relationship between the level of knowledge, family support and the role of cadres with the use of posyandu for the elderly. The process of searching for articles using a search engine in the form of Google Scholar. The analysis of articles uses a compare technique or looks for similarities between several literatures which are then drawn conclusions. The conclusion of this study is that the variables of knowledge, family support and the role of cadres have a relationship with the use of posyandu for the elderly. Suggestions are expected that the role of cadres can provide counseling to the elderly about the benefits of the elderly posyandu so that the elderly can participate in the activities of the elderly posyandu.